ENHANCING MSME'S MARKETING PERFORMANCE THROUGH INNOVATION CAPABILITY MEDIATED BY TECHNOLOGY CAPABILITY AND VALUE-BASED SELLING - Pantjologiningroem, Dewi Sri Woelandari; Vikaliana, Resista; Setyawati, Novita Wahyu (Islamic Economics, Finance, and Banking Review, 2021)
Introduction to The Problem: During the global Covid-19 pandemic, with social restrictions, digital marketing became a demand.  Plenty of MSMEs are unable to adapt to digital marketing quickly. It depends on innovation capabilities and technology capabilities of MSMEs, as well as an understanding of value-based selling.Purpose: This study examines whether innovation capabilities are able to improve MSME marketing performance mediated by technology capabilities and value-based selling.Methodology: A quantitative approach is used in this research with Structural Equation Modeling (SEM) modeling.  The questionnaire was distributed to 39 samples of MSMEs in Java, with purposive sampling..Findings: SEM model testing shows that innovation capabilities have a positive and significant effect on improving the marketing performance of MSMEs, both directly and indirectly. Both technology capabilities and value-based selling are able to mediate the capacity for innovation to improve the marketing performance of MSMEs.   Paper Type: Research Article